CONSTRUCTION AND PRACTICE OF MEDICAL RESPONSIBILITY: DILEMMAS AND NARRATIVES FROM GERIATRICS - KAUFMAN, SHARON R. (Culture, medicine and psychiatry, 1997)
A narrative approach is employed in this article about dilemmas and physician reasoning in geriatric medicine in order to explore the moral-medical worlds of urban American physicians. Reconstructed dilemmas, in the form of stories told by 51 doctors, are analyzed as cultural documents of both clinical-moral knowledge and practice and the physician as moral actor. Discussion focuses on ways in which responsibility is constituted and enacted through a particular language of clinical action. This analysis opens the subject of bioethics to a range of infrequently discussed issues that physicians cite as deeply troubling and contributes to a broadening of anthropological approaches useful in the study of bioethics.